1979
DOI: 10.1093/bja/51.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Metallized Plastic Sheeting in the Prevention of Hypothermia During Neurosurgery

Abstract: Metallized plastic sheeting (m.p.s.) was found to be ineffective in the prevention of hypothermia in adult patients studied during neurosurgical operations. Twenty patients were wrapped in m.p.s. and 22 patients acted as controls. Mean oesophageal temperature in the m.p.s. group decreased from 36.2 degrees C to 35.4 degrees C after 3 h (control 36.5 degrees C to 35.4 degrees C). It was concluded that active warming systems are needed to maintain normothermia in patients undergoing neurosurgical operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…If perspiration condenses on the metallic surface of the reflective blanket, the infra-red reflective property of the surface of the blanket decreases. 12 Glycine 1.5070 solution was heated to 37 QC but this temperature fell rapidly (mean 33.3 QC) once exposed to the theatre ambient . -IIIOf'Sfl/eslU and illlel1$il'£' Care.…”
Section: Discussionmentioning
confidence: 99%
“…If perspiration condenses on the metallic surface of the reflective blanket, the infra-red reflective property of the surface of the blanket decreases. 12 Glycine 1.5070 solution was heated to 37 QC but this temperature fell rapidly (mean 33.3 QC) once exposed to the theatre ambient . -IIIOf'Sfl/eslU and illlel1$il'£' Care.…”
Section: Discussionmentioning
confidence: 99%
“…These rescue sheets are usually used in first aid procedures and are included in many emergency kits. They have also been used to reduce heat loss in human patients during prolonged surgeries with conflicting reports on their efficacy and safety (Radford and Thurlow 1979, Bourke and others 1984). Buggy and Hughes (1994) demonstrated that the use of such sheets decreased the incidence of postanaesthetic shivering and patients’ perception of cold and resulted in higher skin temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Radford and Thurlow found the "Space Blanket" manufactured by Thermos was unable to prevent core hypothermia during neurosurgery. 59 Condensing of perspiration over a long case will reduce the infra-red reflectiveness. This may account for the differing conclusions of the two studies, since the Tyvek 1443 has perforations to avoid moisture trapping whereas the Space Blanket does not.…”
Section: Reflective Blanketsmentioning
confidence: 99%